DEVELOPING THE TECH-DI MODEL: TECHNOLOGY-INTEGRATED DIGITAL ISLAMIC LEARNING FOR AN ISLAMIC EDUCATION MANAGEMENT COURSE - Masita; Ihsanul In’am; Roemlah (Academic Bright Collaboration, 2026)
This study developed a Technology-Integrated Digital Islamic (Tech-DI) model for an Islamic Education Management course at Muhammadiyah University of Bima. The model responds to fragmented platform use, uneven digital readiness, and the need to align educational technology with Islamic ethical commitments. A qualitative developmental design adapted the ADDIE cycle. Evidence was drawn from observation, interviews, questionnaires, focus group discussions, and documents involving 45 undergraduate students, two course lecturers, and seven academic and learning-technology personnel. The analysis identified inconsistent use of learning platforms, varied lecturer and student capability, and limited use of learning data for formative support. The resulting Tech-DI model comprises value-aligned governance, LMS orchestration, digital-competence scaffolding, collaborative feedback, and ethical learning analytics. Implementation evidence indicated more organized material access, participation, academic communication, and formative monitoring. The model is context-specific and requires multi-site validation before broader claims are made. Rather than treating technology as a stand-alone medium, the model embeds digital learning in Islamic educational management, institutional governance, and learner agency.